Vasoactive intestinal peptide stimulates immunoglobulin production and growth of human B cells. - Ishioka, C (1992)
The effect of vasoactive intestinal peptide (VIP) on human lymphoblastoid B cell lines and tonsil B cells was studied. VIP increased immunoglobulin production and proliferation by lymphoblastoid B cell line, GM-1056, in a dose-dependent manner. As little as 10(-12) M of VIP was effective, and higher concentrations of VIP induced an approximately five-fold increase in IgA production. Moreover, this enhancement was blocked by VIP antagonist. Similarly, VIP enhanced IgM and IgG production by other lymphoblastoid B cell lines, CBL and IM-9, respectively. In contrast to VIP, another neuropeptide substance P (SP) or somatostatin failed to enhance immunoglobulin production and thymidine uptake. VIP also enhanced IgA production and thymidine uptake by purified tonsil B cells. However, in contrast to B cell lines, VIP failed to enhance IgM and IgG production by tonsil B cells. SP or somatostatin failed to enhance immunoglobulin production or thymidine uptake by tonsil B cells. These results indicate that VIP acts as B cell stimulatory factor and that VIP may also have preferential effect on IgA production on tonsil B cells.